Empiric slow pathway ablation in non-inducible supraventricular tachycardia. (20th January 2015) - Shurrab, Mohammed; Szili-Torok, Tamas; Akca, Ferdi; Tiong, Irving; Kagal, Darren; Newman, David; Lashevsky, Ilan; Onalan, Orhan; Crystal, Eugene
Abstract: Background: The data supporting the practice of empiric slow pathway ablation (ESPA) in patients with documented supraventricular tachycardia (SVT) who are non-inducible at electrophysiology study (EPS) is limited. The aim of this study is to assess the efficacy of ESPA in adults. Methods: A multi-center cohort study of patients who had ESPA between January 2008 and October 2013 was performed. Patients were identified by screening sequential SVT ablation procedures. Results: Forty-three (5%) out of 859 SVT ablation procedures were identified as ESPA. The median age was 53 (IQR: 24) years; 63% were female. All patients had pre-EPS documentation of SVT (either strip or ECG). In 23 (53.5%) cases, pre-EPS ECG showed short RP tachycardia. Thirty-two (74.4%) patients had dual atrioventricular nodal physiology (DAVNP) plus echo beats. Junctional rhythm (JR) as procedural endpoint was noted in 39 (90.7%) patients. In 18 (41.9%) patients, the abolishment of DAVNP was achieved. No complications were encountered. A median follow-up of 17 months (range: 6 to 31 months) revealed 83.7% (36 of 43) success rate, defined as the absence of pre-procedural symptoms and any documented sustained arrhythmia. As compared to patients with recurrence (n = 7), patients with no recurrence (n = 36) had significantly higher prevalence of clinical short RP tachycardia (61.1% vs. 14.3%, p = 0.038), and EPS finding of DAVNP plus echo beats (80.6% vs. 42.9%, p = 0.034). Conclusions: ESPA is a reasonable approach in patients with documented SVT, in particular in short RP tachycardia, who are not inducible at EPS. Larger studies are required to assess this practice. Highlights: The practice of ESPA is common ( 5-10% of SVT cases). The data to support and guide this practice in adults is limited. This study demonstrates that ESPA is effective in eliminating SVT recurrence. Short RP tachycardia, and/or DAVNP plus echo beats were predictive of success. The procedural endpoint of JR could be a sufficient endpoint in these cases.